The role and regulation of FOXO1 in carbohydrate metabolism and its targeting in metabolic diseases - Ani Retno Prijanti; Ni Made Wiasty Sukanty (Indonesian Archives and Biomedical Sciences, 2021)
Carbohydrate is the first energy source used in metabolic processes. Failure in carbohydrate metabolism can cause metabolic diseases, and many studies are focused on its therapy. Until now, there is no specific therapy approved. Despite that, one of the main alternatives is regarding the involvement of FOXO1 protein in metabolic disease progress. As a transcription factor for gluconeogenesis genes, FOXO1 can increase blood glucose levels. It also involves various signaling pathways in carbohydrate metabolisms such as PI3K/Akt and PKA in which many proteins act as FOXO1 regulators through posttranslational modification. The vital role of FOXO1 in carbohydrate metabolism provides an opportunity to make FOXO1 the main target of metabolic disease therapy. Various proteins and natural compounds can either directly or indirectly regulate FOXO1 activity. It can be an option to be used to control blood glucose levels by targeting FOXO1